Female boxers have high bone mineral density despite low body fat mass, high energy expenditure, and a high incidence of oligomenorrhea - Trutschnigg, B.; Chong, C.; Habermayerova, L.; Karelis, A. D.; Komorowski, J. (Applied Physiology, Nutrition, and Metabolism, 2008)
Low body fat mass and menstrual irregularities have been associated with low bone mineral density (BMD). The aim of this study was to compare the relation between BMD, lean body mass, fat mass, physical activity energy expenditure (PAEE), and menstrual status in female boxers and in physically active females with low (C1) or average (C2) fat mass. Boxers (n = 11) and controls (C1, n = 16; C2, n = 17), aged 18-38 years, were assessed for BMD and body composition with dual-energy X-ray absorptiometry. Menstrual status and PAEE were determined from questionnaires. There was no difference in anthropometric measurements between boxers and C1 subjects, except that boxers had higher arm lean mass. However, both boxers and C1 subjects had a lower percentage of fat (p < 0.001) than C2 subjects (boxers, 14.6% ± 2.0; C1, 15.5% ± 4.2; C2, 25.8% ± 3.4%), and boxers had a higher (p = 0.002) lean body mass index (lean body mass/height2, where lean body mass is measured in kilograms and height is measured in metres) than C2 subjects. The PAEE of boxers was higher (p < 0.007) than that of controls (boxers, 5748 ± 2284 ; C1, 2966 ± 2258 ; C2, 2714 ± 1722 kcal·week-1). Oligomenorrhea was more common in boxers than in C1 and C2 subjects (boxers, 54.6%; C1, 18.8%; C2, 35.3%). Arm, leg, and spine BMD were higher (p < 0.008) in boxers than in C1 subjects, and arm BMD was higher in boxers than in C2 subjects. BMD Z scores were also higher (p < 0.05) in boxers (boxers, 1.1± 0.8, C1, 0.1± 0.7; C2: 0.3 ± 1.1). High BMD in boxers, despite low fat mass, high PAEE, and an increased incidence of oligomenorrhea suggest that boxing has a positive effect on BMD.